Multi-sectoral decomposition in decoupling industrial growth from carbon emissions in the developed Jiangsu Province, China. (15th March 2015) - Lu, Qinli; Yang, Hong; Huang, Xianjin; Chuai, Xiaowei; Wu, Changyan
Abstract: ICE (Industrial carbon emission) is one of most important sources of anthropogenic carbon emissions. To reduce the carbon emissions, many countries, particularly China, have adjusted their industrial structures and improved energy efficiency. The complete decomposition technique and decoupling method were used to investigate and quantitatively analyze the main factors influencing the energy-related ICE in Jiangsu, the Chinese province with the largest energy consumption and carbon emissions. The importance of the sectoral dimension was taken into account by dividing the industry into three main departments consisting of 38 sub-sectors. The results indicated that the industry of Jiangsu was in a weak decoupling state from 2005 to 2012. The industrial output growth was the biggest driver of the increase in ICE, while energy efficiency advancement was the main cause for the reduction, in a weakening trend. The year of 2008 was an important breaking point when the optimization of industry structure came into play and global financial crisis took place. The biggest dilemma in Jiangsu is heavy industry is still dominant, especially the five sectors of them made the biggest contribution (88.2%) to ICE. Thankfully, there were five manufacturing industries had achieved low carbon economy at various degrees. Highlights: Multi-sectoral decomposition and decoupling were conducted to evaluate the ICE. The industry of Jiangsu was in a weak decoupling state with an increasing trend. The industrial output growth was the biggest driver for ICE from 2005 to 2012. The optimization of industry structure came into play for the reduction since 2008. Five backward and advanced industries were identified.